1974
DOI: 10.1073/pnas.71.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Biosynthesis in Nonfibroblastic Cell Lines

Abstract: Prolyl hydroxylase and other enzymes of collagen synthesis have been found in cloned cells, including epithelium, melanoma, liver, HeLa, pituitary, kidney, and neuroblastoma. The significance of collagen biosynthesis in nonfibroblastic cells lines is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…There is now considerable evidence that all cell lines in tissue culture, with the possible exception of lymphomata (Goldberg and Green, 1969), produce collagen and contain prolyl hydroxylase (Langness and Udenfriend, 1974) while in vivo there is evidence that aortic smooth muscle cells produce collagen (Ross and Glomset, 1973). In addition, it has been shown that normal corneal epithelium produces interstitial and basement membrane collagen (Trelstad, Hayashi and Toole, 1974) and that other epithelia produce basement membrane collagen (Pierce, 1970 …”
Section: Discussionmentioning
confidence: 99%
“…There is now considerable evidence that all cell lines in tissue culture, with the possible exception of lymphomata (Goldberg and Green, 1969), produce collagen and contain prolyl hydroxylase (Langness and Udenfriend, 1974) while in vivo there is evidence that aortic smooth muscle cells produce collagen (Ross and Glomset, 1973). In addition, it has been shown that normal corneal epithelium produces interstitial and basement membrane collagen (Trelstad, Hayashi and Toole, 1974) and that other epithelia produce basement membrane collagen (Pierce, 1970 …”
Section: Discussionmentioning
confidence: 99%
“…Although production of collagen decreases when a critically low oxygen level is reached (92), collagen deposition is enhanced with elevated concentrations of lactate (93,94). Therefore, by releasing high levels of lactate (25), macrophages indirectly contribute to collagen formation.…”
Section: Oxygen and Lactatementioning
confidence: 99%
“…In this Opinion article, we focus on how hypoxia affects extracellular matrix (ECM) deposition, remodelling and degradation, which might potentiate cancer metastasis. Central to this emerging paradigm are three crucial findings: the ECM is a dynamic structure that influences tumour progression 1318 ; multiple cell types, including cancer cells, contribute to ECM production 1923 ; and the remodelled ECM within regions of intratumoural hypoxia could be a pathway rather than an obstacle for cancer metastasis 2427 .…”
mentioning
confidence: 99%